“THE SCIENTIFIC HERITAGE OF BUKHARA JADIDS” - Yusupova Laylo Umidbek qizi (Scholars Digest Publishing, 2023)
This article describes the importance of jadidism in the national liberation movements as well as the socio-political situation of the early 20th century, reflecting on the main importance and Princedom of jadidism ideas. The article is enriched on the basis of sources that reveal the uniqueness of the Bukharan jadidism movement.
Keywords: history, culture, spirituality, heritage, cultural heritage, material heritage, national and universal culture, jadidism, enlightenment.